2020
DOI: 10.1002/cpt.2096
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics of Trastuzumab Deruxtecan in Patients With HER2‐Positive Breast Cancer and Other Solid Tumors

Abstract: Trastuzumab deruxtecan (T-DXd; DS-8201) is a HER2-targeting antibody-drug conjugate with a novel enzymecleavable linker, a topoisomerase I inhibitor payload, and a drug-to-antibody ratio of ≈ 8. We have characterized the population pharmacokinetics (PK) of T-DXd and released drug (free DXd) in patients with HER2-positive breast cancer or other solid tumor malignancies. This analysis includes pooled data from 5 clinical studies with 639 patients. T-DXd doses ranged from 0.8 to 8.0 mg/kg every 3 weeks. Serum con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 28 publications
4
39
0
Order By: Relevance
“…DS-8201a showed a favorable rat PK profile despite its relatively high overall hydrophobicity level. This observation is in accordance with previously reported primate PK studies of this ADC, even though a comparison with the native antibody was not provided [ 39 , 55 ]. A possible explanation could be that the PK profile of DS-8201a is favored by the progressive deruxtecan drug-linker deconjugation in plasma over time.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…DS-8201a showed a favorable rat PK profile despite its relatively high overall hydrophobicity level. This observation is in accordance with previously reported primate PK studies of this ADC, even though a comparison with the native antibody was not provided [ 39 , 55 ]. A possible explanation could be that the PK profile of DS-8201a is favored by the progressive deruxtecan drug-linker deconjugation in plasma over time.…”
Section: Discussionsupporting
confidence: 91%
“…To address this issue, we investigated the in vitro cytotoxicity of Tra-Exa-PSAR10 in HER2+ breast (MDA-MB-361) and esophageal (OE-19) cancer cell lines that were rendered resistant to T-DM1. The characterization of T-DM1 resistance mechanisms of these two models demonstrated no alteration of HER2 expression in resistant OE-19 cells, whereas resistant MDA-MB-361 cells demonstrated heterogeneity in HER2 expression when compared to the parental cell line [ 55 , 56 ]. Our results showed that Tra-Exa-PSAR10 circumvented T-DM1-resistance in both cancer models.…”
Section: Discussionmentioning
confidence: 99%
“…Statistically significant covariates (country, tumor size, sex, formulation, age, body weight, albumin, total bilirubin, and aspartate aminotransferase (AST)) resulted in a < 20% change in steady‐state area under the concentration‐time curve (AUC) of intact T‐DXd and released drug, except for increased body weight (95th percentile, 86 kg) and decreased albumin (5th percentile, 31 g/L). Analysis of patients stratified by country, race, renal function, and hepatic function found no clinically meaningful differences in steady‐state exposure of intact T‐DXd or released drug 12 …”
mentioning
confidence: 92%
“…Analysis of patients stratified by country, race, renal function, and hepatic function found no clinically meaningful differences in steady-state exposure of intact T-DXd or released drug. 12 Here, we characterize T-DXd exposure-response relationships with respect to key efficacy and safety end points to further support dose justification of T-DXd in patients with HER2-positive metastatic breast cancer.…”
mentioning
confidence: 99%
See 1 more Smart Citation